Can early childhood education programs support positive outcomes for indigenous children? A systematic review of the international literature. (November 2020) - Elek, Catriona; Gubhaju, Lina; Lloyd-Johnsen, Catherine; Eades, Sandra; Goldfeld, Sharon
Abstract: A robust body of literature demonstrates the positive impact of quality early childhood education on learning and development, particularly for disadvantaged children. This should extend to indigenous children, who often face barriers to positive learning and developmental outcomes. However, research on the impact of early education specifically for indigenous children is sparse. This systematic review of the international literature identified programs in early childhood education settings targeting indigenous children's learning, development and wellbeing. It sought to identify key features of each program and how acceptable they were to the community. Twelve experimental or quasi-experimental studies assessing the impact of 11 programs met the eligibility criteria. All showed promising, if limited, effects on outcomes for indigenous children. The findings suggest there is scope for further rigorous experimental research on the impact of programs which are responsive to local contexts, and which adheres to principles for the conduct of research with indigenous communities. Highlights: Preschool education has the potential for long-term benefits to indigenous children. Twelve studies of eleven preschool programs for indigenous children were identified. Positive impacts on indigenous children's learning and development were found. Further research and more rigorous evaluations of existing programs are required. Programs and research should respond to indigenous contexts and research principles.